2015
DOI: 10.1039/c5py00998g
|View full text |Cite
|
Sign up to set email alerts
|

Tunable LCST behavior of poly(N-isopropylacrylamide/ionic liquid) copolymers

Abstract: Tunable LCST of PNIPAM–IL copolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
155
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(163 citation statements)
references
References 25 publications
(29 reference statements)
4
155
0
4
Order By: Relevance
“…DSC thermogram was obtained with a heating rate of 10°C per min under N 2 purge. The cloud point temperature of the dissolved film, following the method described by Jain et al, 19 was determined by monitoring UV-Vis transmittance at 563 nm (Spectramax M2e microplate reader, Molecular Devices, Sunnyvale, CA, USA) in the temperature range of 25 to 37°C. The wettability of the PNIPAAm- g -polydopamine coated surface was characterized by water contact angle measurements on a goniometer (Krüss G10; KRÜSS GmbH, Hamburg, German).…”
Section: Methodsmentioning
confidence: 99%
“…DSC thermogram was obtained with a heating rate of 10°C per min under N 2 purge. The cloud point temperature of the dissolved film, following the method described by Jain et al, 19 was determined by monitoring UV-Vis transmittance at 563 nm (Spectramax M2e microplate reader, Molecular Devices, Sunnyvale, CA, USA) in the temperature range of 25 to 37°C. The wettability of the PNIPAAm- g -polydopamine coated surface was characterized by water contact angle measurements on a goniometer (Krüss G10; KRÜSS GmbH, Hamburg, German).…”
Section: Methodsmentioning
confidence: 99%
“…Poly(N-isopropylacrylamide) (PNIPAM) exhibiting an LCST at 32 o C, is the most widely studied secondary amide-based polyacrylamides (see the structure in Scheme 1). [19][20][21][22][23][24][25][26][27][28] High-frequency dielectric relaxation technique has shown that the water molecules could form hydrogen bonding with the secondary amide group of PNIPAM or other water molecules, producing hydrogen-bond bridges thus hydrating PNIPAM. 20 When the temperature was above LCST, the PNIPAM precipitated from the solution as a result of the hydrogen-bond bridges being broken.…”
Section: Introductionmentioning
confidence: 99%
“…As for the tertiary amide-based polyacrylamides, it is more difficult to equip the polymers with thermoresponse than the secondary amide-based polyacrylamides due to the complexity to achieve hydrophobic-hydrophilic balance. As a result, one can easily prepare thermoresponsive polymers of the secondary amide polyacrylamides, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] such as poly(N-methacryloyl-L -alanine methyl ester), 33 poly(N-acryloylglycine methyl ester) 34 , poly(N-acryloyl-Lproline methyl ester), 35 poly(N-acryloyl-L -phenylalanine methyl ester) 36 and poly(N-cyclopropylacrylamide), 37 In this work, we design and synthesize a thermoresponsive polymer, poly(N-acryloylsarcosine methyl ester) (PNASME, Scheme 1) with a tertiary amide group in the pendant. And the hydrophobic ester group was employed to counteract the hydrophilic tertiary amide group, making PNASME exhibiting a LCST-type phase transition behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This property of PNIPAM and its copolymers is used for designing of hybrid thermoresponsive drug delivery systems (DDS). In order to adjust the hydrophobicity of PNIPAM and thereby its LCST various random and block copolymers of N-isopropylacrylamide (NIPAM) with different composition and microstructure have been synthesized [8,9]. Copolymerization of NIPAM with different monomers thus allows tuning of the properties especially LCST of PNIPAM according to the requirements of the applications under investigation.…”
Section: Introductionmentioning
confidence: 99%